Effect of Moringa Leaves Water Extract Combined with Collagen and Vitamin C on Malondialdehyde Levels in Rats Exposed to Oxidative Stress - Ginting Suka, Andika Brema Ajudanta; Syarifah, Siti; Saputri, Dewi; Savira, Maya; Kaban, Sri Melinda; Hasni, Dita (Iraqi Journal of Science, 2025)
The increasing prevalence of free radical-related diseases has led to a greater reliance on herbal medicines, such as Moringa oleifera (ML), as antioxidants. However, limited evidence exists regarding the combined effect of herbal and conventional antioxidants on malondialdehyde (MDA) levels. This research assessed simplisia characterization, phytochemical screening, antioxidant activity of ML water extract (ML-WE), and serum MDA levels in animal models using ELISA. Forty-two Wistar rats were randomly divided into seven groups: a negative control, a positive control, and five treatment groups. All treatment groups were exposed to lead for seven days, followed by supplementation with either ML-WE (200 mg/kg BW), vitamin C (36 mg/kg BW), collagen (27 mg/kg BW), or their combinations. ML-WE showed strong antioxidant activity (IC50: 81.761 ppm). MDA levels differed significantly among groups (p < 0.001). Combining ML-WE with collagen reduced MDA levels more than ML-WE alone (14.65 ± 0.66 vs 21.32 ± 0.95 nmol/mL, p < 0.05) but was less effective than collagen monotherapy. Similarly, ML-WE combined with vitamin C showed no statistically significant improvement. These results indicate that while ML-WE has strong antioxidant properties, no synergistic effects were observed in combination therapies.